Plant tissue culture : applications and limitations - Bhojwani, S. S. (Sant Saran) (Developments in crop science, 1990)
During the past decade, Plant Tissue Culture (PTC) has attracted considerable attention because of its vital role in plant biotechnology. PTC offers novel approaches to plant production, propagation, and preservation. Some in vitro techniques are being applied on a commercial scale while many others hold great potential. Consequently, the literature in this area has grown rapidly. This book deals with recent developments in plant tissue culture, and presents a critical assessment of the proven and potential applications of the various in vitro techniques, it also highlights current problems limiting the application of tissue culture, and projects the future lines of research in this field.